Konflik Politik dalam Pemilihan Kepala Desa Sayur Mahincat Tahun 2011 - SIREGAR, SALEH SYAHPUTRA (Politeia: Jurnal Ilmu Politik, 2014)
General election is an important process in democratic countries. Therefore the general election held not only at the central level but also at regional. The village chief elections in the village Sayur Mahincat Kecamatan Aek Nabara Barumun Kabupaten Padang Lawas held on 10 No-vember 2011. This process raises political conflict. This study tried to describe facts about the Sayur Mahincat Village Chief Election (Pemilihan Kepala Desa) in 2011. Specifically looking at the political conflict in village chief elections. This study was conducted with field research techniques. The data analysis of this study uses qualitative analysis. There are three important things underlying the emergence of conflict in the selection of the village chief. First, there are deception in the selection process of village chief candidates; Second, the process of voters data collection have had alot of problems; Third, there are various violation of the village chief candidates during the campaign process.Keywords: Political conflict, elections, political behavior.